Kendala Hukum Dalam Pelaksanaan Strategi Mitigasi Perubahan Iklim Pada Sektor Kehutanan Dan Lahan di Indonesia - Fauziyyah Nur Isya'bani; Sapto Hermawan; Asianto Nugroho (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Indonesia as an achipelagic country has impacts of climate change. To overcome the impacts, Indonesia uses two methods, namely climate change mitigation and adaptation. In accordance with the provisions stipulated in Presidential Regulation No. 98 of 2021 concerning the Implementation of Carbon Economic Values ​​to Achieve Nationally Determined Contribution Targets, the forestry sector is the main sector in controlling emissions to store carbon with a carbon net sink approach from the forestry and land sector in 2030 (Indonesia's FOLU Net Sink 2030) with two targets, namely 29% with own efforts and 41% with international cooperation. This study aims to conduct a legal review of Indonesia’s climate change mitigation strategy by achieving the net sink target in the forestry and land use (FOLU) sector by 2030. This research method use is normative legal research with statue approach. This research use analyse techniques with syllogism method based on deductive. The results indicate that limited specific and integrated regulations, weak law enforcement, implementation of decentralization, to low public awareness of the impact of climate change. However, Indonesia does not have regulations that specifically and comprehensively to regulate climate change. The research concludes that several conditions have impact the achievement of Indonesia’s Forestry and Other Land Use Net Sink target in 2030.